Expression of DNA methyltransferases is involved in Quercus suber cork quality - Ramos, Miguel; Rocheta, Margarida; Carvalho, Luísa; Inácio, Vera; Graça, José; Morais-Cecílio, Leonor (Tree Genetics & Genomes, 2013)
Abstract Cork oak (Quercus suber ) is an important Portuguese species, mainly due to the economic value of the cork it produces. Cork results from phellogen, a meristematic tissue, which can locally produce lenticels or have discontinu- ities, originating “defects”: pores and nail inclusions that are detrimental to cork industrial use. Epigenetic processes control plant development and its deregulation can lead to altered phenotypes; therefore, the study of epigenetic players in the phellogen is important to understand the emergence of cork's defects. DNA methyltransferases (DNMTs) and one protein associated to MET1 (DMAP1) were characterized in Q. suber, and their gene expression was analyzed in phellogen and con- tiguous differentiating cell layers of trees producing high and low quality cork, after the evaluation of their defects by physical and image analysis methods. All classes of DNMTs (MET, DRM, and CMT) with the respective canonical motifs were identified in Q. suber. The expression analyses of these genes showed that QsDRM2 was the most active methyltransferases in the cells analyzed, and that all the genes were differentially expressed in trees with distinct cork quality,with a tendency for higher expression levels in lowquality producers. Interestingly, the global methylation level was higher in cells with low expression of DNA methyltransferases. A positive and significant correlation was obtained between QsDMAP1 gene expression and the percentage of cork defects. This work provides the first evidence that cork quality in Q. suber is likely influenced by epigenetic mechanisms
Keywords: CMT3; Cork oak; Cork quality; DMAP1; DRM; MET1; MET2; phellogen activity

Characterization of Sardinian cork oak (Quercus suber L.) genetic resources for economically important traits - Bullitta, Simonetta; Dettori, Sandro; Manchinu, Manuela; Filigheddu, Maria Rosaria; Piluzza, Giovanna (Genetic Resources and Crop Evolution, 2010)
Considering the very high socio economic value of cork oak (Quercus suber L.) in Mediterranean areas, a better knowledge of local genetic resources is necessary in order to reach a good balance between the conservation issues and the need of an efﬁcient cork production network. In such frame, local germplasm of Q. suber from the main cork production areas of Sardinia was analysed for DNA and isozyme polymorphisms and for cork quality in relation to some environmental parameters. A total number of 24 sample stands of cork oak were selected, representing typical vegetation, sylvicultural and cork quality features within the eight identiﬁed cork growing areas in Sardinia. Considerable variation was found between cork oak stands of the different areas. Results of the principal component analysis performed on the cork quality data and environmental characters of the eight areas, showed that the ﬁrst three components explain 72.2% of the variation. The major characters involved in this differentiation were cork quality characters such as dimensional recover, moisture and Mg content of the cork and also elevation of stands m a.s.l. for the ﬁrst component. The second component appears to be determined by some climatic parameters (average annual temperature and average of the minimum temperatures of coldest month) and by the Fe and Zn in the cork. For the third component, major characters involved in differentiation are average annual rainfall, bark thickness and Ca content in the cork.
Keywords: cluster analysis; Cork quality; DNA polymorphisms; Principal component analysis; Quercus suber L.

Field sampling of cork value before extraction in Portuguese ‘montados’ - Almeida, Alice M.; Tomé, Margarida (Agroforestry Systems, 2009)
The assessment of cork quality and the estimation of cork value are very important to forest landowners, for management purposes and for cork commercialisation. The Forest Producers Associations have been using a sampling scheme with the objective of estimating cork value (price per unit of weight, usually kg) before extraction, based on the sampling of individual trees along a zigzag transect that covers the entire stand. The sampling error is usually too high, but, from a practical standpoint, it is difﬁcult to increase the sampling intensity if it would imply an increase in sampling costs. The aim of this work was to propose, from data collected in six stands representative of the cork oak stands in Portugal, an alternative sampling methodology with a more efﬁcient precision/ cost ratio. Precision and costs of alternative sampling designs based on clusters of different sizes, complemented with analysis of the intracluster correlation coefﬁcient, were studied in order to propose the most adequate sampling strategy. Single-stage cluster sampling with clusters of 5–7 trees guarantees a reasonable sampling error (10–15%) and can be conducted without a large increase in cost.
Keywords: Cork oak; Cork quality; Cork thickness; Cork value; Intracluster correlation coefﬁcient; Single-stage cluster sampling

Field sampling of cork value before extraction in Portuguese ‘montados’ - Almeida, Alice M; Tomé, Margarida (Agroforestry Systems, 2009)
The assessment of cork quality and the estimation of cork value are very important to forest landowners, for management purposes and for cork commercialisation. The Forest Producers Associations have been using a sampling scheme with the objective of estimating cork value (price per unit of weight, usually kg) before extraction, based on the sampling of individual trees along a zigzag transect that covers the entire stand. The sampling error is usually too high, but, from a practical standpoint, it is difﬁcult to increase the sampling intensity if it would imply an increase in sampling costs. The aim of this work was to propose, from data collected in six stands representative of the cork oak stands in Portugal, an alternative sampling methodology with a more efﬁcient precision/ cost ratio. Precision and costs of alternative sampling designs based on clusters of different sizes, complemented with analysis of the intracluster correlation coefﬁcient, were studied in order to propose the most adequate sampling strategy. Single-stage cluster sampling with clusters of 5–7 trees guarantees a reasonable sampling error (10–15%) and can be conducted without a large increase in cost.
Keywords: Cork oak; Cork quality; Cork thickness; Cork value; Intracluster correlation coefﬁcient; Single-stage cluster sampling

Site quality evaluation by classification tree: an application to cork quality in Sardinia - Corona, Piermaria; Dettori, Sandro; Filigheddu, Maria Rosaria; Maetzke, Federico; Scotti, Roberto (European Journal of Forest Research, 2005)
Cork harvesting and stopper production represent a major forest industry in Sardinia (Italy). The target of the present investigation was to evaluate the ‘‘classiﬁcation tree’’ as a tool to discover possible relationships between microsite characteristics and cork quality. Seven main cork oak (Quercus suber) producing areas have been identiﬁed in Sardinia, for a total of more than 122,000 ha. Sixty-three sample trees, distributed among diﬀerent geographical locations and microsite conditions, were selected. A soil proﬁle near each sample tree was described, soil samples were collected and analysed. After debarking, cork quality of each sample tree was graded by an independent panel of experts. Microsites where trees had more than 50% of the extracted cork graded in the best quality class, according to the oﬃcial quality standard in Italy, were labelled as prime microsites, the others as nonprime microsites. Relationships between a binary dummy variable (0 for nonprime microsites, 1 for prime microsites) and site factors were investigated using classiﬁcation tree analysis to select the relevant variables and to deﬁne the classiﬁcation scheme. Prime quality microsites for cork production proved to be characterised by elevation, soil phosphorus content and sandiness. Results have been compared with those of the more conventional parametric approach by logistic regression. The work demonstrates the advantages of the classiﬁcation tree method. The model may be appropriate for classiﬁcations at landscape and stand mapping levels, where it is possible to sample a number of microsites and to evaluate distributional characteristics of model output, while its precision is only indicative when estimating the prime quality of single microsites.
Keywords: Classiﬁcation tree; Cork quality; Logistic regression; Quercus suber; Site classiﬁcation and evaluation

Site quality evaluation by classification tree: an application to cork quality in Sardinia - Corona, Piermaria; Dettori, Sandro; Filigheddu, Maria Rosaria; Maetzke, Federico; Scotti, Roberto (European Journal of Forest Research, 2005)
Cork harvesting and stopper production represent a major forest industry in Sardinia (Italy). The target of the present investigation was to evaluate the ‘‘classiﬁcation tree’’ as a tool to discover possible relationships between microsite characteristics and cork quality. Seven main cork oak (Quercus suber) producing areas have been identiﬁed in Sardinia, for a total of more than 122,000 ha. Sixty-three sample trees, distributed among diﬀerent geographical locations and microsite conditions, were selected. A soil proﬁle near each sample tree was described, soil samples were collected and analysed. After debarking, cork quality of each sample tree was graded by an independent panel of experts. Microsites where trees had more than 50% of the extracted cork graded in the best quality class, according to the oﬃcial quality standard in Italy, were labelled as prime microsites, the others as nonprime microsites. Relationships between a binary dummy variable (0 for nonprime microsites, 1 for prime microsites) and site factors were investigated using classiﬁcation tree analysis to select the relevant variables and to deﬁne the classiﬁcation scheme. Prime quality microsites for cork production proved to be characterised by elevation, soil phosphorus content and sandiness. Results have been compared with those of the more conventional parametric approach by logistic regression. The work demonstrates the advantages of the classiﬁcation tree method. The model may be appropriate for classiﬁcations at landscape and stand mapping levels, where it is possible to sample a number of microsites and to evaluate distributional characteristics of model output, while its precision is only indicative when estimating the prime quality of single microsites.
Keywords: Classiﬁcation tree; Cork quality; Logistic regression; Quercus suber; Site classiﬁcation and evaluation

APLICACION DEL ANALISIS DE IMAGENES AL ESTUDIO DE PARÁMETROS MORFOMETRICOS DEL CORCHO - Campos, M.; Molinas, M. (Scientia gerundensis, 1999)
In this work we propose a method to study cork quality from little samples throug the analy- sis of images. This method has aplications in all studies that need cork quality determination. The digital analysis of images is an apropiate option due to makes morphometry automati- cally and it allows a quick manipulation of the results. It is a fast and objective method because allows the comparative study between a high number of samples; so it could be pos- sible to compare populations or individual in order to study the influence of some ambiental or getnetic factors and have another aproach to three's selection. Here we describe an digital analysis program based on IMAGE 1.41 VDMi software for Macintosh developed to measu- re severa1 cork morphometric parameters.
Keywords: Cork quality; image analysis; methodology; morphometry; Quercus suber

APLICACION DEL ANALISIS DE IMAGENES AL ESTUDIO DE PARÁMETROS MORFOMETRICOS DEL CORCHO - Campos, M; Molinas, M (Scientia gerundensis, 1999)
In this work we propose a method to study cork quality from little samples throug the analy- sis of images. This method has aplications in all studies that need cork quality determination. The digital analysis of images is an apropiate option due to makes morphometry automati- cally and it allows a quick manipulation of the results. It is a fast and objective method because allows the comparative study between a high number of samples; so it could be pos- sible to compare populations or individual in order to study the influence of some ambiental or getnetic factors and have another aproach to three's selection. Here we describe an digital analysis program based on IMAGE 1.41 VDMi software for Macintosh developed to measu- re severa1 cork morphometric parameters.
Keywords: Cork quality; image analysis; methodology; morphometry; Quercus suber

Variabilidad de los factores de calidad para el corcho en plancha. - GONZÁLEZ ADRADOS, J R; GONZÁLEZ HERNÁNDEZ, J F; SIMÓN SERFATY, L; Adrados, L E Z; Hern, L E Z; Apdo, Serfaty Cifor-inia (II Congreso Forestal Español, 1997)
Main parameters affecting cork production and quality (thickness, apparent density, surface density, annual growth and porosity) are studied. Data from a sample of 105 pieces of cork (20 cm x 20 cm size) collected in seven different sites are analysed. Sites are considered as representative of the most common Spanish Quercus suber stands. Means and standard deviations of this parameters are presented for the different quality grades obtained by manual classification, focusing on the effect of grading on porosity and density. The effect of site factor on density and annual growth is also studied.
Keywords: Annual Growth; Cork; Cork Production; Cork quality; Density; Porosity; Quercus suber

APLICACION DEL ANALISIS DIGITAL DE IMAGENES AL ESTUDIO DE LA CALIDAD DEL CORCHO - Molinas, M; Campos, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Digital Image Processing and Analysis (lA) es a computerized technique that permits to measure defined regions of interest of an image. For Al, digital images of the specimens are examined with appropiate software programs. In the present study an lA program for the quuantitative anatomy of cork has been developed. For this purpose IMAGE 1.41 VDM software for Macinstosh and Statview statistic software have been selected. Specimens from different cork populatins have been compared. The following cork parmeters: thickness, cork-rings and prososity have been measured in transverse and tangential sections. The results are analysed comparatively on each population and between populations.
Keywords: Cork quality; image analysis; morphometry; Quantitative anatomy; Quercus suber L.

EL ARCHIVO DE MUESTRAS DE CORCHO Y SU USO PARA LA OBSERVACION DE LA INFLUENCIA DE DETERMINADOS FACTORES SOBRE LA CALIDAD - Gamero Guerrero, F (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Annually, between April and July, is carry out the estimation in field of Cork Quality Works. That consist in several random sampling in those plots which turn cutting is over in the current year. In IPROCOR, since prepared and stored the samples obtained, are b~ing carried out, to define possible relations between several silvicultural and industrial operations and environmental factors, and cork quality, a set of measures and observations
Keywords: Cork; Cork quality

FACTORES QUE DETERMINAN LA CALIDAD DEL CORCHO - González Adrados, José Ramón (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Cork quality, strongly related with economical profit 9f Quercus suber stands, is today determined by the visual characteristics of corkwood planks, mainly porosity and thickness. Variance in those'parameters is imputed to ecologic?l, selvicultural and genetic factors. Relationship between environmental factors and cork qua lit y is studied in this work. Data from two samples obteined in Extremadura and Catalonia show that this dependence is significati ve.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Cork; Cork quality; Quercus suber stands

FACTORES QUE DETERMINAN LA CALIDAD DEL CORCHO - González Adrados, José Ramón (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Cork quality, strongly related with economical profit 9f Quercus suber stands, is today determined by the visual characteristics of corkwood planks, mainly porosity and thickness. Variance in those'parameters is imputed to ecologic?l, selvicultural and genetic factors. Relationship between environmental factors and cork qua lit y is studied in this work. Data from two samples obteined in Extremadura and Catalonia show that this dependence is significati ve.
Keywords: Cork; Cork quality; Quercus suber stands

POTENCIALIDAD DEL TERRITORI0 PARA EL ALCORNOQUE EN EXTREMADURA - GONZÁLEZ ADRADOS, J R; Elena Rosselló, R; Tella Ferreiro, G (Scientia gerundensis, 1992)
Most important aspects of a work titled 4ork oak Atlas of Extremaduran are presented here. A set of maps about: cork oak stands distribution; cork quality in the several zones; and ecological factors wich may limit the appearence of cork oak stands, are elaborated from the availahle thematic cartography. The Geographical Information SystemPC-ARC-IhFO ha beenused to get it. The final result is the Land Suitability for Cork Oak and Cork Quality Map of Extremadura. This map defines for the whole studied area the relative cork quaiity to be obteined and the presence of ecological factors wich may be adverse or exclusive for cork oak.
Keywords: Cork oak; Cork quality; land classification; Quercus suber; thematic cartography

POTENCIALIDAD DEL TERRITORI0 PARA EL ALCORNOQUE EN EXTREMADURA - González Adrados, J. R.; Elena Rosselló, R.; Tella Ferreiro, G. (Scientia gerundensis, 1992)
Most important aspects of a work titled 4ork oak Atlas of Extremaduran are presented here. A set of maps about: cork oak stands distribution; cork quality in the several zones; and ecological factors wich may limit the appearence of cork oak stands, are elaborated from the availahle thematic cartography. The Geographical Information SystemPC-ARC-IhFO ha beenused to get it. The final result is the Land Suitability for Cork Oak and Cork Quality Map of Extremadura. This map defines for the whole studied area the relative cork quaiity to be obteined and the presence of ecological factors wich may be adverse or exclusive for cork oak.
Keywords: Cork oak; Cork quality; land classification; Quercus suber; thematic cartography